2021
DOI: 10.3390/antiox10091408
|View full text |Cite
|
Sign up to set email alerts
|

Stemness of Human Pluripotent Cells: Hypoxia-Like Response Induced by Low Nitric Oxide

Abstract: The optimization of conditions to promote the stemness of pluripotent cells in vitro is instrumental for their use in advanced therapies. We show here that exposure of human iPSCs and human ESCs to low concentrations of the chemical NO donor DETA/NO leads to stabilization of hypoxia-inducible factors (HIF-1α and HIF-2α) under normoxia, with this effect being dependent on diminished Pro 402 hydroxylation and decreased degradation by the proteasome. Moreover, the master genes of pluripotency, NANOG and OCT-4, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 49 publications
3
12
0
Order By: Relevance
“…In this line, for the first time, our group studied the effect of low NO on the hypoxia response in human PSCs (hPSCs). We found that the treatment with low NO doses promotes HIF-1α and HIF-2α protein accumulation in hPSCs cultured under normoxic conditions (21% O 2 ), mimicking the hypoxia response in cells cultured at 5% of O 2 in a hypoxia incubator [14] (Figure 2B). We also revealed an increase in the expression of NANOG and OCT-4 mRNA and protein levels in human iPSCs exposed to a low dose of DETA-NO in normoxia when compared with untreated cells.…”
Section: The Role Of Nitric Oxide In Metabolic Signature In Stem Cell...mentioning
confidence: 59%
See 4 more Smart Citations
“…In this line, for the first time, our group studied the effect of low NO on the hypoxia response in human PSCs (hPSCs). We found that the treatment with low NO doses promotes HIF-1α and HIF-2α protein accumulation in hPSCs cultured under normoxic conditions (21% O 2 ), mimicking the hypoxia response in cells cultured at 5% of O 2 in a hypoxia incubator [14] (Figure 2B). We also revealed an increase in the expression of NANOG and OCT-4 mRNA and protein levels in human iPSCs exposed to a low dose of DETA-NO in normoxia when compared with untreated cells.…”
Section: The Role Of Nitric Oxide In Metabolic Signature In Stem Cell...mentioning
confidence: 59%
“…Considering these preliminary results, we proposed low doses of NO under normoxic conditions could activate a response similar to hypoxia; and that this activation may be responsible for the mechanism by which NO promotes pluripotency and delays differentiation into ESCs and iPSCs. In this line, we recently described the essential role of NO inducing a cellular response to hypoxia in PSCs [14].…”
Section: Nitric Oxide and Pluripotencymentioning
confidence: 98%
See 3 more Smart Citations